The effect of management control system on the relationship between budget participation and budget slack - Sangkala, Masnawaty (2015)
The objective of this study is to examine the effect of budget participation on budget slack in Indonesian manufacturing firms. The study also investigates the moderating effect of the management control system on the relationship between budget participation and budget slack. Based on Simons’s four levers of control, budget participation and management control system are considered have significant influenced on budget slack. This study used questionnaires to collect the data. Questionnaires were distributed to functional managers such as finance managers, production managers and marketing managers, which represents 34.22 percent of the response rate. Factor analysis, linear regression analysis and hierarchical multiple regression analysis are used to analyze the data.The finding of the study indicates that there is a negative relationship between budget participation and budget slack, which suggesting that participate in budgeting process can reduce budget slack. There is also a negative relationship between budget participation and each of the management control system elements (which are interactive control system, boundary control system, diagnostic control system and beliefs control system) on budget slack. The result also shows that the management control system either as a package or an element negatively moderates the relationship between budget participation and budget slack. The results suggest that management control systems are applicable in assisting firms to reduce the dysfunctional behavior among managers. The result also proposes that management control system constitutes a crucial factor that impact on the reduction of budget slack. The results of the study are also expected to have implications on the importance of managers in manufacturing sector to participate in the budgeting process and integrate it with management control system to reduce budget slack.